Analytical Modeling of the Postcracking Response Observed in Hybrid Steel/Polypropylene Fiber-Reinforced Concrete - Caggiano, Antonio (2020)
This study deals with the analytical modeling of hybrid fiber-reinforced concretes (HyFRCs) made with a blend of different types of fibers characterized by different geometries and/or constitutive materials. The presented analytical formulation is oriented towards predicting the postcracking behavior of HyFRC and is mainly based on the well-known "cracked-hinge" model originally employed for standard fiber-reinforced concrete beams. The proposed model is validated by considering the experimental results obtained in a previous study carried out on HyFRCs mixtures made with a blend of steel and polypropylene fibers. Theoretical results are presented to demonstrate the predictive capabilities of the model to simulate the observed experimental behavior. The model performance is in very good agreement with the experimental data. Therefore, it has the capability to forecast the postcracking behavior of a generic HyFRC of given fiber contents depending on the actual proportion of the fiber blend. Finally, the proposed formulation can be applied as a computational aid to the design of HyFRC mixtures for structural purposes.